Artificial Intelligence and International Relations Theories - Ndzendze, Bhaso; Marwala, Tshilidzi (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
XIII, 165 p. 30 illus., 1 illus. in color.